2019
DOI: 10.1021/acs.inorgchem.8b03526
|View full text |Cite
|
Sign up to set email alerts
|

Proton Conduction in Organically Templated 3D Open-Framework Vanadium–Nickel Pyrophosphate

Abstract: A new proton-conducting material (C6H14N2)­[NiV2O6H8(P2O7)2]·2H2O (1) was hydrothermally synthesized by using 1,4-diazabicyclo­[2,2,2]­octane (DABCO) as the template. Its inorganic framework, determined by single crystal X-ray diffraction, is constructed by the connection of V/NiO6 octahedral to P2O7 pyrophosphate units through sharing oxygen atoms, giving rise to three-dimensional (3D) intersecting 6-, 8-, and 12-ring channels along the [100], [010], and [001] directions, respectively, in which there are orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The spectral bands at 1671, 1600, and 3461–2947 cm –1 are ascribed to the bending and tensile vibrations of the N–H and O–H groups. , The charge balance of the structure was verified by BVS bond valence theory calculations (Table S4), which confirmed the presence of B­(III), Ni­(II), and V­(IV) in the crystal. In addition, the presence of V and Ni was further confirmed by an XPS analysis of compound 1 and the result of the test (Figure S4) showed that the valence state of the V ion was V 4+ and that of the Ni ion was Ni 2+ , which is consistent with reports in the literature. Its crystallographic data are shown in Table S1.…”
Section: Resultsmentioning
confidence: 69%
“…The spectral bands at 1671, 1600, and 3461–2947 cm –1 are ascribed to the bending and tensile vibrations of the N–H and O–H groups. , The charge balance of the structure was verified by BVS bond valence theory calculations (Table S4), which confirmed the presence of B­(III), Ni­(II), and V­(IV) in the crystal. In addition, the presence of V and Ni was further confirmed by an XPS analysis of compound 1 and the result of the test (Figure S4) showed that the valence state of the V ion was V 4+ and that of the Ni ion was Ni 2+ , which is consistent with reports in the literature. Its crystallographic data are shown in Table S1.…”
Section: Resultsmentioning
confidence: 69%
“…As demonstrated in Table , the highest σ of 1 is comparable to that of Nafion and several conductive materials of COF­(TfBD) (3.0 × 10 –1 S/cm, 80 °C and 95% RH), PSM 1 (1.67 × 10 –1 S/cm, 80 °C and 95% RH), MOF­(Co) (1.49 × 10 –1 S/cm, 80 °C and 98% RH), H 3 PO 4 @S1–15 (1. 37 × 10 –1 S/cm, 30 °C and 100% RH), and BUT-8­(Cr)­A (1.27 × 10 –1 S/cm, 80 °C and 100% RH) and higher than that of a few of efficient proton conducting materials with high conductivities around 10 –2 S/cm. ,,,,, Also, the highest proton conductivity of 2 can be comparable with the above high proton conducting materials under similar testing conditions. ,,,,, …”
Section: Resultsmentioning
confidence: 89%
“…S1, ESI†). 33 The absorption band observed in the UV spectrum of VB-1 (Fig. S2, ESI†) indicates charge transfer within the [V 6 B 20 ] cluster unit.…”
Section: Resultsmentioning
confidence: 99%
“…S1, ESI †). 33 The absorption band observed in the UV spectrum of VB-1 (Fig. S2 34,35 The experimental PXRD pattern presented in Fig.…”
Section: Synthesis Crystal Structure and Characterization Of Vb-1mentioning
confidence: 99%